Pro Oracle Spatial for Oracle database 11g - Kothuri, Ravi, 1972- (Expert's voice in Oracle., 2007)
Pro Oracle Spatial for Oracle Database 11g shows how to take advantage of Oracle Databases built-in feature set for working with location-based data. A great deal of the information used in business today is associated with location in some way, and analysis of that data is becoming ever more important in today's mobile and highly connected world. In Pro Oracle Spatial for Oracle Database 11g, authors Ravi Kothuri and Albert Godfrind address: The special nature of spatial data and its role in professional and consumer applications Issues in spatial data management such as modeling, storing, accessing, and analyzing spatial data The Oracle Spatial solution and the integration of spatial data into enterprise databases How spatial information is used to understand business and support decisions, to manage customer relations, and to better serve private and corporate users When you read Pro Oracle Spatial for Oracle Database 11g, you're learning from the very best. Ravi Kothuri is a key member of Oracle's Spatial development team. Albert Godfrind consults widely with Oracle clients on the implementation of Oracle Spatial, develops training courses, and presents frequently at conferences. Together they have crafted a technically sound and authoritative fountain of information on working with spatial data in the Oracle database.